The Effect of Specific Regions Exercises on Performance Endurance Development of Youth Soccer Players - Karrar Ibrahim Bader; Muhammad Jasim Othman (College of Physical Education and Sport Sciences, 2021)
Soccer is considered the sports that required endurance, speed of performance. The study aimed at designing exercises for developing performance endurance in youth soccer players. The researcher was applied on (20) youth soccer players rom Al Jawia sport club (2020 - 2021) aged (17 - 19) years old divided into two equal groups. The program was applied for (8) weeks that consisted of exercises for developing performance endurance in youth soccer players. The data was collected and treated using proper statistical operations to conclude that these exercises positively affect posttests.